Developing and Testing the Validity and Reliability of the Brief Adolescent Respiratory System Health Assessment Scale-Student Version in a Chinese Sample - Tao, Lingwei; Gao, Yana; Dou, Hongzhe; Wu, Xuekun; Yan, Lu; Liu, Danyang; Zhao, Yuejia; Zhao, Qingchun; Wang, Peiyu; Zhang, Yumei (Frontiers in Pediatrics, 2021)
Objectives: To develop a Brief Adolescent Respiratory System Health Assessment Scale-Student Version (BARSHAS-SV) and test the validity and reliability of the scale. Methods: Considering common respiratory system diseases and respiratory system symptoms as a theoretical basis, researchers developed a Brief Adolescent Respiratory System Health Assessment Scale-Student Version-Ⅰ(BARSHAS-SV-Ⅰ). After six medical experts reviewed the BARSHAS-SV-Ⅰ, and six adolescents tested the BARSHAS-SV-Ⅰ, researchers developed an updated BARSHAS-SV-Ⅱ. Researchers randomly selected two middle schools in Baoding, China. 1029 valid questionnaires were recovered. Researchers evaluated the validity and reliability of the scale and obtained the final version of the scale (BARSHAS-SV). The exploratory factor analysis (EFA) and the confirmatory factor analysis (CFA) were used to evaluate the construct validity of the scale. The content validity index (CVI) was used to evaluate the content validity of the scale. The Cronbach’s  coefficient and the mean inter-item correlation coefficient (MIIC) were used to assess the reliability of the scale. Results: BARSHAS-SV Cronbach’s  = 0.910, content validity = 0.941, and factor cumulative variance contribution rate = 64.047% conducting EFA. Conducting CFA, Chi square value (χ2) = 233.806, degrees of freedom (df) = 106, Chi square value/degree of freedom (χ2/df) = 2.206, root-mean-square error of approximation (RMSEA) = 0.063, normed fit index (NFI) = 0.922, goodness of fit index (GFI) = 0.917, Tueker-Lewis index (TLI) = 0.942, comparative fit index (CFI) = 0.955, incremental fit index (IFI) = 0.956. BARSHAS-SV consisted of 4 dimensions and 17 items. Four factors were as follows: Factor 1, mild respiratory system diseases (Cronbach’s  coefficient = 0.781); Factor 2, severe respiratory system diseases (Cronbach’s  coefficient = 0.829); Factor 3, respiratory system symptoms (Cronbach’s  coefficient = 0.835); Factor 4, treatment and recovery of respiratory system diseases (Cronbach’s  coefficient = 0.845). Conclusions: BARSHAS-SV is a valid and reliable method that can be applied to assess adolescent respiratory system health status. BARSHAS-SV may help teachers and medical staff in schools to quickly and conveniently evaluate the adolescent respiratory system health status and identify respiratory issues.